EPISTEMOLOGI TAFSIR MAQASIDI - Kusmana, Kusmana (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This article examines tafsîr maqâ?idî in epistemological outlook. It studies the origins, methodology, and validation of its construction. Based on depth literary analysis, this article argues that tafsîr maqâ?idî cannot be separated from its origins in the historical development of Islamic law. It can be seen from the rise of tafsîr maqâ?idî that is much more originated and established from maqâ?id al-sharî?ah in terms of Islamic law. The basic framework of tafsîr maqâ?idî is not only developed by Muslim scholars who are well educated in Islamic law such as Ibn ?Âshûr and Jaser Auda, but also initiated by scholars of theology such like Mu?ammad ?Abduh and Mu?ammad Rashîd Ri?â. The article also suggests that the movement of maqâ?id al-sharî?ah thoughts including tafsîr maqâ?idî has relevant effort in constructing Islamic knowledge which is well known in contemporary Islamic discourse as islamization of knowledge. On the origins, tafsîr maqâ?idî is like tafsir bi al-ra?y that attempts to find a logical basis and methods that is appropriate to Islamic sources, and on the same time it tries to put a logic and reason as the basis for interpretation. On methodological side, tafsîr maqâ?idî is built in two traces of tafsir tradition that is well known as naqlî and ?aqlî methods. And on validation, tafsîr maqâ?idî forms itself into a wide creativity in using naqlî and ?aqlî methods by emphasizing on rational and empirical study with special reference to ma?âli? mursalah.